Experience of conflict in the dual role of nurses in career path - Dannyanto, Diandra Nur; Astari, Asti Melani; Lestari, Retno (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
The dual role conflict experienced by female nurses is an unavoidable phenomenon. On the one hand, nurses have a burden of responsibility at work, but on the other hand, they also have to carry out their role in the family. This situation has an impact on the emergence of conflict within nurses in carrying out these roles which leads to efforts to increase career levels. This research aims to explore the experience of conflict in the dual role of nurses in advancing their career path at the Unisma Islamic Hospital in Malang. This research uses a qualitative research design. Participants in this study consisted of 6 nurses who had career positions as team heads. Data collection in this research used semi-structured interviews with data analysis consisting of 4 stages, namely reduction, data presentation, conclusion drawing, and verification. The results of research on the conflict between the dual roles of nurses in advancing career paths at the Unisma Islamic Hospital in Malang produced 3 themes, namely the difficulty of nurses in fulfilling their work responsibilities; nurses' difficulty in managing time; and nurses feel that the demands of the tasks given are unbalanced.  This research resulted in findings that the conflict between the dual roles of nurses in their career path takes the form of a conflict in balancing the roles of nurses in family and work. In the family, nurses have responsibilities towards parents, husbands and children, while work requires performance and education to support professional career paths. Abstrak: Konflik peran ganda yang dialami perawat perempuan merupakan fenomena yang tidak dapat dihindari. Perawat di satu sisi mempunyai beban tanggung jawab dalam bekerja, namun di sisi lain juga harus menjalankan perannya dalam keluarga. Keadaan ini berdampak pada munculnya konflik dalam diri perawat dalam menjalankan peran tersebut yang berujung pada upaya peningkatan jenjang karir. Penelitian ini bertujuan untuk mengeksplorasi pengalaman konflik peran ganda perawat dalam memajukan jenjang karir di Rumah Sakit Islam Unisma Malang. Penelitian ini menggunakan desain penelitian kualitatif. Partisipan dalam penelitian ini terdiri dari 6 orang perawat yang mempunyai jabatan karir sebagai kepala tim. Pengumpulan data dalam penelitian ini menggunakan wawancara semi terstruktur dengan analisis data yang terdiri dari 4 tahap yaitu reduksi, penyajian data, penarikan kesimpulan, dan verifikasi. Hasil penelitian konflik peran ganda perawat dalam memajukan jenjang karir di Rumah Sakit Islam Unisma Malang menghasilkan 3 tema yaitu sulitnya perawat dalam memenuhi tanggung jawab pekerjaannya; kesulitan perawat dalam mengatur waktu; dan perawat merasa tuntutan tugas yang diberikan tidak seimbang. Penelitian ini menghasilkan temuan bahwa konflik peran ganda perawat dalam jalur karirnya berupa konflik keseimbangan peran perawat dalam keluarga dan pekerjaan. Dalam keluarga, perawat mempunyai tanggung jawab terhadap orang tua, suami dan anak, sedangkan pekerjaan memerlukan kinerja dan pendidikan untuk mendukung jalur karir profesional.